Population structure and predation in the harvester termite, Trinervitermes trinervoides (Sjöstedt).cwwpirk@zoology.up.ac.za - Pirk, Christian Walter Werner (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 2013.